Non-linear Dose Response of Lymphocyte Cell Lines to Microtubule Inhibitors - Potashnikova, Daria M.; Saidova, Aleena A.; Tvorogova, Anna V.; Sheval, Eugene V.; Vorobjev, Ivan A. (Frontiers in Pharmacology, 2019)
Microtubule (MT) inhibitors show anti-cancer activity in a wide range of tumors in vitro and demonstrate high clinical efficacy. To date they are routinely included into many chemotherapeutic regimens. While the mechanisms of MT inhibitors’ interactions with tubulin have been well-established, the relationship between their concentration and effect on neoplastic cells is not completely understood. The common notion is that tumor cells are most vulnerable during division and all MT inhibitors block them in mitosis and induce mitotic checkpoint-associated cell death. At the same time multiple evidence of more subtle effects of lower doses of MT inhibitors on cell physiology exist. The extent of efficacy of the low-dose MT inhibitor treatment and the mechanisms of resulting cell death currently present a critical issue in oncology. The prospect of MT inhibitor dose reduction is promising as protocols at higher concentration have multiple side effects. We assessed cell cycle changes and cell death induced by MT inhibitors (paclitaxel, nocodazole and vinorelbine) on human lymphoid B-cell lines in a broad concentration range. All inhibitors had similar accumulation effects and demonstrated “trigger” concentrations that induce cell accumulation in G2/M phase. Concentrations slightly below the “trigger” promoted cell accumulation in sub-G1 phase. Multi-label analysis of live cells showed that the sub-G1 population is heterogeneous and may include cells that are still viable after 24 hours of treatment. Effects observed were similar for cells expressing Tat-protein. Thus cell cycle progression and cell death are differentially affected by high and low MT inhibitor concentrations.